High-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable and preparation method thereof
By using a multiphase system of modified high-density polyethylene, neoprene, low-density polyethylene and modified fillers in the sheath layer materials of industrial robot cables, the problem of insufficient performance of the cable under harsh conditions is solved, and the comprehensive performance improvement of high softness, high strength, low temperature resistance, wear resistance and chemical corrosion resistance is achieved.
Patent Information
- Application Number
- CN202510085007.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing industrial robot cables are difficult to maintain high performance and long life under harsh conditions such as high frequency mechanical stress, low temperature environment and chemical corrosion, and there are problems of insufficient bending strength, low temperature resistance, wear resistance and chemical corrosion resistance.
A sheath layer material composed of modified high-density polyethylene, neoprene, low-density polyethylene and modified fillers is used to form a multiphase system through specific weight ratios and processing processes to improve the bending strength, low temperature resistance, wear resistance and chemical corrosion resistance of the cable.
It significantly improves the bending strength, low temperature resistance, wear resistance and chemical corrosion resistance of the cable, extends the service life, reduces maintenance and replacement frequency, and reduces operating costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application belongs to the field of cable technology, and specifically relates to a highly flexible, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable and a preparation method thereof. Background Art
[0002] Industrial robot cables are special cables designed specifically for industrial robots and their automation systems. They need to maintain high performance and long life in harsh working environments.
[0003] Cables for industrial robots are one of the key components to ensure the normal operation of the robot system. However, the cables for industrial robots on the market still have the following problems: 1. Industrial robots usually need to perform frequent repetitive movements, such as rotation, bending, and extension. Cables must be able to withstand this high-frequency mechanical stress without breaking or being damaged. The internal structure of the robot is compact, and the cables may need to pass through narrow spaces or complex paths. Highly flexible cables can adapt to these space limitations more easily and reduce the difficulty of installation. 2. Robot cables may be subjected to forces such as tension, compression, and torsion during movement. High-strength cables can withstand these mechanical stresses and avoid breakage or deformation caused by external forces. High-strength cables can maintain stable performance during long-term use, reduce maintenance and replacement frequency, and reduce operating costs. 3. Some industrial robots may need to work in low-temperature environments, such as cold storage, freezing workshops, or cold outdoor areas. Low-temperature resistant cables can maintain good flexibility and mechanical properties under low-temperature conditions to avoid embrittlement or breakage caused by temperature changes. In low-temperature environments, ordinary materials tend to accelerate aging and affect the electrical performance of cables. Low-temperature resistant cables can extend service life and ensure long-term stable power transmission and signal transmission. 4. Industrial robots may be used in industries such as chemical, pharmaceutical, and food processing, where various chemicals such as acids, alkalis, solvents, and detergents exist. Chemically resistant cables can maintain insulation and mechanical strength under these harsh conditions, preventing short circuits or damage caused by chemical erosion. 5. Since robot cables often come into contact with machine parts or other objects, wear resistance is also an important characteristic. Wear-resistant cables can reduce surface damage and extend service life.
[0004] PE (polyethylene) is a thermoplastic and is widely used as an insulating sheath material for cables. The existing technology mainly improves the flexibility of the material by adding EVA (ethylene-vinyl acetate copolymer) to the material, but there is a problem of poor compatibility with the base material, which leads to poor mechanical properties of the material.
[0005] Therefore, there is an urgent need for a highly flexible, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable and a preparation method thereof. Summary of the invention
[0006] The purpose of the present application is to provide a highly flexible, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable and a preparation method thereof.
[0007] In order to achieve the above objectives, this application provides the following technical solutions: A high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable, which comprises a cable core, an insulating layer, a buffer layer and a sheath layer from the inside to the outside, wherein the sheath layer material used in the sheath layer comprises the following components in parts by weight: 50-66 parts of modified high-density polyethylene, 15-30 parts of chloroprene rubber, 20-35 parts of low-density polyethylene, 6-12 parts of modified filler, 5-10 parts of carbon black, 22-27 parts of flame retardant, 1-3 parts of antioxidant, 3-5 parts of compatibilizer, 1.4-2 parts of vulcanizer and 1.2-1.6 parts of antioxidant; Furthermore, the raw materials for preparing the modified high-density polyethylene include high-density polyethylene, polyvinyl chloride and urea-formaldehyde resin in a weight ratio of 1: (0.2-0.4): (0.5-0.8).
[0008] Furthermore, the preparation method of the modified high-density polyethylene comprises the following steps: adding high-density polyethylene, polyvinyl chloride and urea-formaldehyde resin in a weight ratio of 1: (0.2~0.4): (0.5~0.8) into a high-speed mixer, stirring and mixing at high speed until uniform, adding the mixture into a single-screw extruder, extruding and granulating the mixture at 180~190°C and a screw speed of 40~50r / min and drying the mixture to obtain the modified high-density polyethylene.
[0009] The present application improves the bending strength of the protective layer of the cable by modifying high-density polyethylene with polyvinyl chloride and urea-formaldehyde resin. In the composite system of high-density polyethylene and polyvinyl chloride, urea-formaldehyde resin can fill the gaps between high-density polyethylene and polyvinyl chloride particles to enhance the interface bonding between them. In addition, the cross-linked network of urea-formaldehyde resin can also limit the movement of high-density polyethylene chain segments, improve the rigidity and modulus of the material, and the three work synergistically to improve its bending strength.
[0010] Furthermore, the weight ratio of the modified high-density polyethylene, chloroprene rubber and low-density polyethylene is (50-55): (18-23): (27-32).
[0011] In the system of the present application, when the modified high-density polyethylene, chloroprene rubber, and low-density polyethylene are in a specific weight ratio, the low-temperature resistance of the cable protective layer can be improved, and good low-temperature brittleness can be maintained at minus 50°C, which is beneficial for the operation of industrial robots in cold environments. Analysis shows that in the system of the present application, the modified high-density polyethylene, chloroprene rubber, and low-density polyethylene form a multiphase system under this condition. Through reasonable proportioning and processing technology, these components can form an ideal mesostructure on a microscopic scale. Chloroprene rubber can form a continuous elastic phase, while high-density polyethylene and low-density polyethylene form a semi-crystalline matrix phase. This multiphase structure can effectively disperse stress at low temperatures and prevent stress concentration, thereby improving the material's resistance to low temperatures. At the same time, under this condition, the aging resistance of the cable is improved.
[0012] The chloroprene rubber was purchased from Shanxi Huochang Changhua Synthetic Rubber Co., Ltd., model: chloroprene rubber CR121. The high-density polyethylene was purchased from Merck Darmstadt, Germany, item number 547999. The low-density polyethylene was purchased from Merck Darmstadt, Germany, item number 428043.
[0013] Furthermore, the preparation method of the modified filler comprises the following steps: (1) mixing lanthanum oxide, silicon dioxide and carbon nanotubes in a weight ratio of 1: (1.4-1.6): (0.3-0.5) to obtain a mixture; (2) Dissolve 20-30 parts by weight of alkyd resin in 300 parts by weight of tetrahydrofuran, add 50 parts by weight of the mixture, stir for 1-2 hours under ultrasonic action, pour into 600-700 parts by weight of anhydrous ethanol, precipitate, filter out, wash the precipitate with anhydrous ethanol, and dry to obtain a modified filler.
[0014] Furthermore, the particle size of the lanthanum oxide is 30nm~50nm, and the specific surface area is 30~50m 2 / g. The average particle size of the silicon dioxide is 10nm and the average specific surface area is 380m 2 / g. The carbon nanotube has an inner diameter of 10-20nm, a tube length of 5-15μm, and a specific surface area of 120-180m 2 / g of multi-walled carbon nanotubes.
[0015] The present application improves the wear resistance of the cable protective layer by adding modified fillers to the sheath layer material, and at the same time improves the corrosion resistance of the cable protective layer. In the modified filler, lanthanum oxide, silicon dioxide and carbon nanotubes form a multiphase composite system. Through reasonable proportioning, these components can be evenly dispersed on a microscopic scale to form an ideal mesostructure and a dense composite phase. The alkyd resin further enhances the interface bonding force, the hardness and wear resistance of the material by wrapping the filler and using the uniform dispersion and close combination between the modified filler and other components in the system.
[0016] Furthermore, the vulcanizing agent is sulfur.
[0017] Furthermore, the flame retardant is decabromodiphenylethane.
[0018] Furthermore, the antioxidant is antioxidant 1010.
[0019] Furthermore, the antioxidant includes one of antioxidant 4020, antioxidant 1010, and antioxidant 224.
[0020] Furthermore, the compatibilizer is maleic anhydride grafted polyethylene.
[0021] The present application provides a method for preparing a high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable, comprising the following steps: (1) mixing the components of the sheath layer material, adding them into a twin-screw extruder, and extruding and granulating them to obtain the sheath layer material; (2) Drawing the copper core into a thin copper wire, taking 6 to 10 thin copper wires and twisting them into a conductor, wrapping 1 to 3 layers of mica tape on the surface of the conductor to form an insulating layer to obtain a cable core, filling the surface of the cable core with artificial fiber to form a filling layer, taking 3 to 5 filled cable cores to form a conductor, adding the sheath layer material to a twin-screw extruder, and extruding it onto the surface of the conductor, the extrusion thickness is 0.2 to 0.4 cm, and the inner diameter is 0.6 to 0.8 cm, thereby forming a protective layer on the surface of the conductor to obtain a cable.
[0022] Compared with the prior art, the advantages and beneficial effects of this application are: 1. The present application improves the bending strength of the protective layer of the cable by modifying high-density polyethylene with polyvinyl chloride and urea-formaldehyde resin.
[0023] 2. In the system of the present application, when the modified high-density polyethylene, chloroprene rubber and low-density polyethylene are in a specific weight ratio, the low-temperature resistance of the cable protective layer can be improved. At the same time, the aging resistance of the cable is improved under this condition.
[0024] 3. The present application can improve the wear resistance of the cable protective layer by adding modified fillers to the sheath layer material, and at the same time improve the corrosion resistance of the cable protective layer. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0026] The raw materials used in the following examples of this application are all commercially available products: Chloroprene rubber was purchased from Shanxi Huochang Changhua Synthetic Rubber Co., Ltd., model: Chloroprene rubber CR121.
[0027] High-density polyethylene was purchased from Merck KGaA, Darmstadt, Germany, catalog number 547999.
[0028] Low-density polyethylene was purchased from Merck KGaA, Darmstadt, Germany, with a product number of 428043. The vulcanizing agent was sulfur.
[0029] The flame retardant is decabromodiphenylethane.
[0030] The antioxidant is antioxidant 1010. Jiangsu Xinluda Polymer Materials Co., Ltd.
[0031] The antioxidant is antioxidant 1010. Nantong Xinchang Chemical Co., Ltd.
[0032] The compatibilizer is maleic anhydride grafted polyethylene, Germany, brand CERONAS, model ADDIMER 630R.
[0033] Polyvinyl chloride was purchased from Xinjiang Tianye Group Co., Ltd. PVC~SG5.
[0034] Urea-formaldehyde resin was purchased from Hubei Xinghengye Technology Co., Ltd., with a solid content of 50 wt%.
[0035] Alkyd resin, purchased from Walker VOK®-S39X70 Alkyd Resin.
[0036] Example 1 The present embodiment provides a high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable, which includes, from the inside to the outside, a cable core, an insulation layer, a buffer layer and a sheath layer. The sheath layer material used in the sheath layer includes the following components in parts by weight: 52 parts of modified high-density polyethylene, 20 parts of chloroprene rubber, 30 parts of low-density polyethylene, 10 parts of modified filler, 8 parts of carbon black, 25 parts of flame retardant, 2 parts of antioxidant, 4 parts of compatibilizer, 1.9 parts of vulcanizer and 1.4 parts of antioxidant.
[0037] The preparation method of the modified high-density polyethylene comprises the following steps: adding high-density polyethylene, polyvinyl chloride and urea-formaldehyde resin in a weight ratio of 1:0.3:0.7 into a high-speed mixer, stirring and mixing at high speed, adding the mixture into a single-screw extruder, extruding and granulating at 185° C. and a screw speed of 45 r / min, and drying to obtain the modified high-density polyethylene.
[0038] The preparation method of the modified filler comprises the following steps: (1) mixing lanthanum oxide, silicon dioxide and carbon nanotubes in a weight ratio of 1:1.5:0.4 to obtain a mixture; (2) Dissolve 25 parts by weight of alkyd resin in 300 parts by weight of tetrahydrofuran, add 50 parts by weight of the mixture, stir for 1.5 hours under ultrasonic action, pour into 650 parts by weight of anhydrous ethanol, precipitate, filter out, wash the precipitate with anhydrous ethanol, and dry to obtain a modified filler.
[0039] The particle size of the lanthanum oxide is 30nm~50nm, and the specific surface area is 30~50m 2 / g. Purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd. The average particle size of the silicon dioxide is 10nm, and the average specific surface area is 380m 2 / g, Jinlei Technology, JL~SiO2~N10. The carbon nanotube has an inner diameter of 10~20nm, a tube length of 5~15μm, and a specific surface area of 120~180m 2 / g multi-walled carbon nanotubes were purchased from Shanghai Maoguo Nanotechnology Co., Ltd.
[0040] The method for preparing the high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable comprises the following steps: (1) Mixing the components of the sheath layer material, adding them into a twin-screw extruder, extruding and granulating at an extrusion temperature of 190° C., and obtaining the sheath layer material; (2) The copper core is drawn into a thin copper wire, 8 thin copper wires are twisted into a conductor, 2 layers of mica tape are wrapped on the surface of the conductor to form an insulating layer to obtain a cable core, and artificial fiber is filled on the surface of the cable core to form a filling layer. 4 filled cable cores are taken to form a conductor, and the sheath layer material is added to a twin-screw extruder and extruded onto the surface of the conductor. The extrusion thickness is 0.2 cm and the inner diameter is 0.6 cm, thereby forming a protective layer on the surface of the conductor to obtain a cable.
[0041] Example 2 The present embodiment provides a high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable, which includes, from the inside to the outside, a cable core, an insulation layer, a buffer layer and a sheath layer, and the sheath layer material used in the sheath layer includes the following components in parts by weight: 50 parts of modified high-density polyethylene, 18 parts of chloroprene rubber, 32 parts of low-density polyethylene, 6 parts of modified filler, 10 parts of carbon black, 22 parts of flame retardant, 3 parts of antioxidant, 3 parts of compatibilizer, 2 parts of vulcanizer and 1.2 parts of antioxidant.
[0042] The preparation method of the modified high-density polyethylene comprises the following steps: adding high-density polyethylene, polyvinyl chloride and urea-formaldehyde resin in a weight ratio of 1:0.2:0.8 into a high-speed mixer, stirring and mixing at high speed, adding the mixture into a single-screw extruder, extruding and granulating at 180° C. and a screw speed of 50 r / min, and drying to obtain the modified high-density polyethylene.
[0043] The preparation method of the modified filler comprises the following steps: (1) mixing lanthanum oxide, silicon dioxide and carbon nanotubes in a weight ratio of 1:1.4:0.3 to obtain a mixture; (2) Dissolve 20 parts by weight of alkyd resin in 300 parts by weight of tetrahydrofuran, add 50 parts by weight of the mixture, stir for 2 hours under ultrasonication, pour into 600 parts by weight of anhydrous ethanol, precipitate, filter out, wash the precipitate with anhydrous ethanol, and dry to obtain a modified filler.
[0044] The particle size of the lanthanum oxide is 30nm~50nm, and the specific surface area is 30~50m 2 / g. Purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd. The average particle size of the silicon dioxide is 10nm, and the average specific surface area is 380m 2 / g, Jinlei Technology, JL~SiO2~N10. The carbon nanotube has an inner diameter of 10~20nm, a tube length of 5~15μm, and a specific surface area of 120~180m 2 / g multi-walled carbon nanotubes were purchased from Shanghai Maoguo Nanotechnology Co., Ltd.
[0045] The method for preparing the high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable comprises the following steps: (1) Mixing the components of the sheath layer material, adding them into a twin-screw extruder, extruding and granulating at an extrusion temperature of 190° C., and obtaining the sheath layer material; (2) The copper core is drawn into a thin copper wire, 8 thin copper wires are twisted into a conductor, 2 layers of mica tape are wrapped on the surface of the conductor to form an insulating layer to obtain a cable core, and artificial fiber is filled on the surface of the cable core to form a filling layer. 4 filled cable cores are taken to form a conductor, and the sheath layer material is added to a twin-screw extruder and extruded onto the surface of the conductor. The extrusion thickness is 0.2 cm and the inner diameter is 0.6 cm, thereby forming a protective layer on the surface of the conductor to obtain a cable.
[0046] Example 3 The difference between this embodiment and embodiment 1 is that the weight ratios of the modified high-density polyethylene, chloroprene rubber and low-density polyethylene are different.
[0047] The sheath layer material used in the sheath layer includes the following components in parts by weight: 60 parts of modified high-density polyethylene, 22 parts of chloroprene rubber, 20 parts of low-density polyethylene, 10 parts of modified filler, 8 parts of carbon black, 25 parts of flame retardant, 2 parts of antioxidant, 4 parts of compatibilizer, 1.9 parts of vulcanizer and 1.4 parts of antioxidant.
[0048] Comparative Example 1 The difference between this comparative example and Example 1 is that the modified high-density polyethylene is replaced by high-density polyethylene purchased from Merck KGaA, Darmstadt, Germany, with a product number of 547999.
[0049] Comparative Example 2 The difference between this comparative example and Example 1 is that the preparation method of the modified high-density polyethylene comprises the following steps: adding high-density polyethylene, polyvinyl chloride and urea-formaldehyde resin in a weight ratio of 1:0.5:0.5 into a high-speed mixer, stirring and mixing at high speed until uniform, adding the mixture into a single-screw extruder, extruding and granulating at 180°C and a screw speed of 45 r / min and drying to obtain modified high-density polyethylene.
[0050] Comparative Example 3 The difference between this comparative example and Example 1 is that the preparation method of the modified filler is different.
[0051] (1) mixing lanthanum oxide, silicon dioxide and carbon nanotubes in a weight ratio of 1:1.5:0.4 to obtain a mixture; (2) 1 part by weight of the mixed material, 0.2 parts by weight of silane coupling agent KH550, 6 parts by weight of water and 4 parts by weight of ethanol were mixed evenly, reacted at 45° C. for 4 h, centrifuged, washed and dried to obtain a modified filler.
[0052] Comparative Example 4 The difference between this comparative example and Example 1 is that lanthanum oxide, silicon dioxide and carbon nanotubes are mixed in a weight ratio of 1:1:1 to obtain a mixture.
[0053] Comparative Example 5 The difference between this comparative example and Example 1 is that the particle size of the lanthanum oxide is 1 μm to 5 μm, and the specific surface area is 1 to 10 m 2 / g. Purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd. The average particle size of silicon dioxide is 20nm and the average specific surface area is 240m 2 / g, Jinlei Technology, JL~SiO2~N20; the carbon nanotubes have an inner diameter of 15~30nm; a tube length of 10~30μm, and a specific surface area of 50~80m 2 / g multi-walled carbon nanotubes were purchased from Xianfeng Nano.
[0054] Performance Testing The performance tests were performed on the protective layers prepared in Examples 1-3 and Comparative Examples 1-5.
[0055] 1. Bending strength test: The sheath material is processed into a long strip sample of 80mm×10mm×4mm. The bending strength performance test standard refers to GB / T9341-2008. The bending strength test is carried out on the XHW-S2000N electronic digital tensile tester. The test rate is 2mm / min and the span is 64mm. Each sample is tested 5 times and the average value is calculated.
[0056] 2. Wear resistance test: The sheath material is processed into a strip sample of 80mm×10mm×4mm, and the strip sample is tested for wear. The test standard for wear refers to GB / T5478-2008. During the test, the weights on both sides are 1000g each, 5000 circles, the speed is 60rpm / min, and the disc with Ø100mm and thickness of 3mm is tested on the Labbot LBT-5612 plastic taber linear wear tester. Each sample is tested 5 times and the average value is calculated.
[0057] 3. Low temperature brittleness: The sheath material is processed into a long strip specimen of 80mm×10mm×4mm, and the sheath material is tested to see whether it breaks at -50℃ according to ASTMD746.
[0058] 4. Aging resistance: The elongation at break test refers to the standard GB / T1040. The aging condition is to treat it at 60℃ for 150h. The elongation at break before and after aging is measured = (elongation at break after aging - elongation at break before aging) / elongation at break before aging * 100%.
[0059] 5. Corrosion resistance: The cable sheath is immersed in 40g / L sodium hydroxide solution at 23±2℃ for 3 days in accordance with IEC60811 for alkali corrosion resistance test, and the change rate of elongation at break after immersion is calculated = (elongation at break after immersion - elongation at break before immersion) / elongation at break before immersion * 100%.
[0060] The results are shown in Table 1.
[0061] Table 1 Performance test results From the above performance test results, it can be seen that the bending strength, corrosion resistance, wear resistance and aging resistance of the cable protective layer of Examples 1 to 3 are excellent, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the components. However, it can be found that the weight ratio of modified high-density polyethylene, chloroprene rubber and low-density polyethylene in Example 3 is not within the range of (50-55): (18-23): (27-32), and the low-temperature resistance and aging resistance of the cable protective layer are reduced, indicating that only the addition of specific modified high-density polyethylene, chloroprene rubber and low-density polyethylene in the system of this application can have excellent low-temperature resistance at -50°C.
[0062] However, the comparative examples are significantly inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the high-density polyethylene is not modified, and in comparative example 2, the ratio of high-density polyethylene, polyvinyl chloride and urea-formaldehyde resin is changed, and the bending strength of the protective layer of the cable is reduced. This shows that only when the high-density polyethylene is modified with polyvinyl chloride and urea-formaldehyde resin in a specific ratio can the bending strength of the protective layer of the cable be improved. In comparative example 3, the preparation method of the modified filler is different, and the wear resistance and corrosion resistance of the cable protective layer are reduced, indicating that the modification method of the present application makes the filler more compatible in the system, and has better wear resistance and corrosion resistance. In comparative examples 4 and 5, the ratio and parameters of the fillers are changed, and the wear resistance and corrosion resistance of the cable protective layer are reduced to varying degrees. The above experimental results further prove the importance of the technical solution defined in the present application for its technical effect.
[0063] The above is a preferred embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles described in the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.
Claims
1. A high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable, characterized in that: The cable core, the insulating layer, the buffer layer and the sheath layer are sequentially included from the inside to the outside. The sheath layer material used in the sheath layer includes the following components in parts by weight: 50-66 parts of modified high-density polyethylene, 15-30 parts of chloroprene rubber, 20-35 parts of low-density polyethylene, 6-12 parts of modified filler, 5-10 parts of carbon black, 22-27 parts of flame retardant, 1-3 parts of antioxidant, 3-5 parts of compatibilizer, 1.4-2 parts of vulcanizer and 1.2-1.6 parts of antioxidant; The raw materials for preparing the modified high-density polyethylene include high-density polyethylene, polyvinyl chloride and urea-formaldehyde resin in a weight ratio of 1: (0.2-0.4): (0.5-0.8).
2. The high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable according to claim 1 is characterized in that: The weight ratio of the modified high-density polyethylene, chloroprene rubber and low-density polyethylene is (50-55): (18-23): (27-32).
3. The high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable according to claim 1 is characterized in that: The preparation method of the modified filler comprises the following steps: (1) mixing lanthanum oxide, silicon dioxide and carbon nanotubes in a weight ratio of 1: (1.4-1.6): (0.3-0.5) to obtain a mixture; (2) Dissolve 20-30 parts by weight of alkyd resin in 300 parts by weight of tetrahydrofuran, add 50 parts by weight of the mixture, stir for 1-2 hours under ultrasonic action, pour into 600-700 parts by weight of anhydrous ethanol, precipitate, filter out, wash the precipitate with anhydrous ethanol, and dry to obtain a modified filler.
4. The high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable according to claim 3 is characterized in that: The particle size of the lanthanum oxide is 30nm~50nm, and the specific surface area is 30~50m 2 / g; the average particle size of the silicon dioxide is 10nm, and the average specific surface area is 380m 2 / g; the inner diameter of the carbon nanotube is 10-20nm; the tube length is 5-15μm, and the specific surface area is 120-180m 2 / g of multi-walled carbon nanotubes.
5. The high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable according to claim 1 is characterized in that: The preparation method of the modified high-density polyethylene comprises the following steps: adding high-density polyethylene, polyvinyl chloride and urea-formaldehyde resin in a weight ratio of 1: (0.2-0.4): (0.5-0.8) into a high-speed mixer, stirring and mixing at high speed until uniform, adding the mixture into a single-screw extruder, extruding and granulating at 180-190° C. and a screw speed of 40-50 r / min and drying to obtain the modified high-density polyethylene.
6. The high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable according to claim 1 is characterized in that: The vulcanizing agent is sulfur; and the flame retardant is decabromodiphenylethane.
7. The high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable according to claim 1 is characterized in that: The antioxidant is antioxidant 1010.
8. The high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable according to claim 1 is characterized in that: The antioxidant includes one of antioxidant 4020, antioxidant 1010, and antioxidant 224.
9. The high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable according to claim 1 is characterized in that: The compatibilizer is maleic anhydride grafted polyethylene.
10. A method for preparing the high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) mixing the components of the sheath layer material, adding them into a twin-screw extruder, and extruding and granulating them to obtain the sheath layer material; (2) The copper core is drawn into a thin copper wire, 6 to 10 thin copper wires are twisted into a conductor, 1 to 3 layers of mica tape are wrapped on the surface of the conductor to form an insulating layer to obtain a cable core, and artificial fiber is filled on the surface of the cable core to form a filling layer. 3 to 5 filled cable cores are taken to form a conductor, and the sheath layer material is added to a twin-screw extruder and extruded onto the surface of the conductor to form a protective layer on the surface of the conductor to obtain a high-flexibility, high-strength, low-temperature-resistant and chemical-corrosion-resistant industrial robot cable.